Multiplicity in supervision relationships: A factor in improving throughput success? - van Biljon, JA; de Kock, E (South African Journal of Higher Education, 2011)
Supervision has been identified as an important factor in the success of postgraduate students, even as the most significant variable and a large number of studies have been conducted to identify factors that contribute to supervision success. However the dependent variable in these studies – supervision success – has been an elusive one to define. The aim of this article is to investigate one aspect of supervision success, namely throughput success. We isolate two factors (gender and home language) pertaining to the student profile and one factor (multiplicity) pertaining to supervision practice and then investigate the association between the factors and through put success. Multiplicity is a term defined here to distinguish the practice of solo supervision (one supervisor) from that of having co-supervision. The methodology includes both quantitative and qualitative strategies with a survey and interviews as the data capturing methods. The main contribution is to highlight the impact of multiplicity on throughput success. This research should be of interest to researchers, supervisors and academic planners.